The endless cycle of pornography addiction: Study among generation Z - Sukmayadi, Qolbi Mujahidillah Adzimat; Fadhila, Sarah Annisa; Febrianti, Adinda Aulya; Putri, Meiliani Maulidia; Nurjanah, Kholidah Zein; Sukmayadi, Vidi (Interaksi: Jurnal Ilmu Komunikasi, 2025)
This qualitative study was conducted to explore the lived experiences of Generation Z struggling with online pornography addiction within Indonesia’s conservative yet digitally connected environment. The study responded to the rising prevalence of internet pornography consumption among this generation. This study employed a phenomenological approach to investigate subjective meanings and behavioral patterns. Data were collected through in-depth interviews with nine participants selected via purposive and snowball sampling. Analysis was conducted using the Interpretative Phenomenological Analysis (IPA) framework, aided by QDA Miner Lite. Cognitive Dissonance Theory was used to understand participants lived experiences, particularly internal conflicts between their behaviors and the values they held. The analysis identified four main themes: 1) the momentum of triggering a desire to watch online pornography; 2) the contribution of online media in escalating pornography access; 3) pornography addiction as a regressive development; and 4) non-solutive compensation efforts and the cycle of pornography addiction. The research findings revealed that online pornography serves as an emotional escape and a socially embedded behavior influenced by peer dynamics and digital culture. The study recommends the development of empathy-based education and counseling programs that emphasize behavioral understanding rather than prohibitive measures.